Field trapping of the flathead oak borer Coroebus undatus (Coleoptera: Buprestidae) with different traps and volatile lures - Fürstenau, Benjamin; Quero, Carmen; Riba, Josep Ma; Rosell, Gloria; Guerrero, Angel (Insect Science, 2014)
The flathead oak borer Coroebus undatus F. (Coleoptera: Buprestidae) is one of the primary pests of cork oak Quercus suber L. in the Mediterranean region causing great economic losses to the cork industry. Very little is known about its biology and behavior and, so far, no control measures have been established. We present the results of a pilot study aimed to develop an efficient trapping method for monitoring this harmful pest. In a 3-year field study, purple-colored prism traps baited with a mixture of green leaf volatiles (GLVs) from the host have been shown the most effective combination to catch C. undatus adults (solely females) compared to other trap and lure types tested. Wavelength and reflectance measurements revealed that purple traps exhibit reflectance peak values similar to those found in the abdominal and elytral cuticle of both sexes, suggesting the involvement of visual cues for mate location in this species. The data presented are the first to demonstrate captures of adults of the genus Coroebus by an attractant-based trapping method.
Keywords: attractants; Buprestidae; Coroebus undatus; Green leaf volatiles; monitoring; Quercus suber

Electrophysiological and behavioral responses of the black-banded oak borer, Coroebus florentinus, to conspecific and host-plant volatiles. - Fürstenau, Benjamin; Rosell, Gloria; Guerrero, Angel; Quero, Carmen (Journal of chemical ecology, 2012)
Aspects of the chemical ecology of the black-banded oak borer, (BBOB) Coroebus florentinus (Coleoptera: Buprestidae), were studied. Odors produced by males and females were similar, both qualitatively and quantitatively. Nonanal, decanal, and geranylacetone, identified in the headspace of both sexes, elicited strong electroantennographic responses from male antennae, but not from female antennae. In dual-choice olfactometer experiments, a blend of these three compounds was attractive to both sexes; males responded to decanal alone, while females responded to geranylacetone alone, suggesting that these compounds are responsible for activity of the blend to the respective sexes. Antennae of both sexes responded electroantennographically to the green leaf volatiles (E)-2-hexenal, (E)-2-hexenol, 1-hexanol, (Z)-3-hexenyl acetate, and n-hexyl acetate, all identified from the host plant Quercus suber. In behavioral experiments, only females were attracted to host-plant odors, and in tests with synthetic compounds, females were attracted to (E)-2-hexenol, 1-hexanol, and (Z)-3-hexenyl acetate. It is likely that these compounds play a role in foraging and/or oviposition behavior of BBOB females.
The following values have no corresponding Zotero field: accession-num: 22477026
Keywords: Aggregation behavior; Black-banded oak borer; Buprestidae; Coleoptera; Cork pest; Coroebus florentinus; Electrophysiology; Green leaf volatiles; Kairomone; Quercus suber; Semiochemicals; Y-tube olfactometer